The Trap Experiment of Scientists: Why Science Cannot Step Outside Spacetime - Hamidi, Nabil (My University, 2025)
Modern science has achieved enormous explanatory success by isolating variables, controlling environments, and analyzing phenomena as independent systems. Yet this methodology contains an often-unacknowledged assumption: that consciousness, information, ideas, beliefs, culture, social systems, and even philosophical concepts can be examined as if they operate apart from spacetime. Scientists routinely discuss these phenomena as though they could theoretically exist without the spatio-temporal field that enables them. The purpose of the trap experiment is to reveal that such separation is epistemologically impossible. Scientists, their instruments, their language, their models, and the very phenomena they study exist entirely inside spacetime. Therefore, any attempt to demonstrate that something is independent of spacetime presupposes an observational position that scientists do not and cannot possess. This article formulates the trap experiment as an analytical argument: if empirical science is trapped within spacetime, then its claims about what might exist outside spacetime — or independently of it — cannot be experimentally verified.